Expression of the interleukin 6 receptor in primary renal cell carcinoma. Issue 10 (October 1997) - Costes, V; Liautard, J; Picot, M C; Robert, M; Lequeux, N; Brochier, J; Baldet, P; Rossi, J F
Abstract : AIMS: Interleukin 6 (IL-6) is expressed in the majority of renal cell carcinomas and has an important role in the proliferation of some renal cell carcinoma cell lines. This action is mediated by two membrane proteins, gp80 (the IL-6 receptor; IL-6R), which binds IL-6, and gp130, which transduces the signal. The soluble form of gp80 (sIL-6R) is able to activate gp130 when complexed to the IL-6 molecule. These considerations prompted an investigation of IL-6R expression in this malignancy. IL-6, C reactive protein (CRP), and sIL-6R were also measured in serum and correlated to clinical and pathological features. METHODS: Immunostaining was performed on cryostat sections from renal cell carcinoma tumours with M91, an anti-IL-6R monoclonal antibody, using the alkaline phosphatase antialkaline phosphatase technique. The proliferation index was measured using the KI-67 monoclonal antibody. CRP, IL-6, and sIL-6R were measured in serum before nephrectomy, using an immunoenzymatic or immunoradiometric assay. RESULTS: There were significant differences in survival in patients with tumours larger than 8 cm, metastasis at diagnosis, high nuclear grade tumours, detectable serum concentrations of IL-6 (correlated to CRP serum concentration), more than 4% proliferating cells, and the presence of the IL-6R in situ. Furthermore, the serum IL-6 concentration correlated with tumour size and stage. The mean serum sIL-6R concentration was not significantly different from that observed in 40 normal subjects. Tumour IL-6R expression was present in 10 samples. There was a significant association between the presence of the IL-6 receptor in tumours and tumour stage, nuclear grade, proliferation index, and serum IL-6. CONCLUSIONS: This study revealed the importance of IL-6/CRP and IL-6R expression in situ as potential new prognostic factors and opens the way to new therapeutic strategies in renal cell carcinoma.